Cam Jansen and the mystery of the stolen diamonds - Adler, David A.; Natti, Susanna (New York : Viking Press, 1980)
A fifth-grader with a photographic memory and her friend Eric help solve the mystery of the stolen diamonds.
G12
Keywords: Mystery and detective stories